Singularity Analysis for a Class of Porous Medium Equation with Time-Dependent Coefficients - Anyin Xia; Xianxiang Pu; Shan Li (Advances in Mathematical Physics)
This paper concerns the singularity and global regularity for the porous medium equation with time-dependent coefficients under homogeneous Dirichlet boundary conditions. Firstly, some global regularity results are established. Furthermore, we investigate the blow-up solution to the boundary value problem. The upper and lower estimates to the lifespan of the singular solution are also obtained here.